Bioinspired asymmetric synthesis of (-)-gymnothelignan v - Darunee Soorukram (2019)
© 2018 American Chemical Society. A bioinspired asymmetric total synthesis of a structurally unique subtype of lignan, namely, (-)-gymnothelignan V, was achieved. The key synthetic sequences involved reduction of the eupomatilone skeleton leading to (-)-gymnothelignan J followed by the formation of the corresponding oxocarbenium ion and stereoselective intramolecular Friedel-Crafts reaction. Our synthetic approach provides the information to support the plausible biosynthetic pathway of this structurally unusual lignan. On a similar basis, other structurally related natural and non-natural gymnothelignans including (-)-gymnothelignan D, 6,9-bis-epi-gymnothelignan V, and 5-epi-gymnothelignans D and J were readily prepared.